Hearing impairment in patients with rheumatoid arthritis: association with anti-citrullinated protein antibodies. Issue 9 (September 2016) - Lobo, Fabrício; Dossi, Mario; Batista, Lígia; Shinzato, Márcia
Abstract It has been suggested that hearing impairment (HI) is one of the extra-articular features of rheumatoid arthritis (RA). Nevertheless, the prevalence and nature of HI in RA is still uncertain. The objectives were to study hearing function in patients with RA using audiometric tests and to examine whether HI correlates with autoantibodies. Hearing functions were investigated in 43 consecutive RA patients and 23 control subjects (less than 60 years old). Their sera were evaluated for the presence of rheumatoid factor (RF), anti-cyclic citrullinated peptide (anti-CCP), and anti-mutated citrullinated vimentin (anti-MCV) antibodies. HI was observed in 46.5 % of RA patients and in 30.4 % of control subjects, p  = 0.32. HI was characterized as sensorineural in 80 and 85.7 % of RA patients and control subjects with HI, respectively, p  = 1.00. RA patients had a worse hearing threshold for air conduction at 6 kHz in the right ear (p  = 0.019) and had a decreased amplitude of otoacoustic emissions (OAEs) at 2 kHz bilaterally (p  = 0.04) compared with control subjects. In the RA group, patients with and without HI were 80 and 34.78 % anti-CCP positive, respectively, p  = 0.008. RA patients with and without HI were 85 and 43.48 % anti-MCV positive, respectively, p  = 0.013. HI in RA patients was mainly sensorineural and was associated with anti-CCP and anti-MCV antibodies.